Description of a new species of Smithophis Giri et al. 2019 (Serpentes: Colubridae: Natricinae) from Arunachal Pradesh, India - Das, Abhijit; Deepak, V.; Captain, Ashok; Wade, Edward O. Z.; Gower, David J. (Zootaxa, 2020)
A new species of the natricine snake genus Smithophis Giri et al. 2019 is described based on three specimens collected from Arunachal Pradesh, India. An additional three referred specimens are documented. Smithophis arunachalensis sp. nov. differs from all known congeners by a combination of 4–5 (rarely 6) small scales around the eye (excluding labial scales), presence of temporal scales, and a distinctive colour pattern of a blackish dorsum and bright yellow venter that form a sharply-defined zigzag border. The new species is known only from ca. 100 km2 in Lower Dibang Valley and Changlang Districts in eastern Arunachal Pradesh. A revised key to the identification of the species of Smithophis is presented.